SONGS-DUETS IN THE CREATION OF EUGEN DOGA - MUNTEANU, ANGELICA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2020)
In the creation of the famous composer Eugen Doga, a special place is occupied by the pop songs that brought the master recognition all over the world. Among the solo songs, the composer wrote also duets. This article contains an overview of the duet-songs signed by E. Doga, as well as the analysis of some of the most representative pieces that are examined both in terms of form, content of the poetic text and musical language, and in terms of the vocal-artistic aspect. The author presents information on the performing versions of some relevant creations — „Oglinda clipelor”, „Flori de dragoste”, „Vreau să cânt”, „Gelozie”. The purpose of the article is to promote Eugen Doga's duet-songs for including them in the concert and didactic repertoire.